(3eLehYI ahGFO aj aVd GdUhe hGdUGFe hBOGHg haVd GdeaWQjf ddabQGAs
(3ChdgG (B:s
(3aGFOI ef TQM GdHNGQi ddMGaX Hf MLQ GdYSbdGfi ai HGH aVd GdUhe s
(3BNQgG (B:s
(3hTgQ QeVGf TgQ Gddg aGMaXhG ajg CfaSce GHf UUQi ai CeGdjg Yf CHj EeGeI GfJgi s
(3GdfSNI HgG MhGTs
(3HBNQg aGFOgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI (B(9325) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs